The Belief In Hantu In The Malay Culture From The Perspective Of Islam - Mohd Zohdi Mohd Amin; Mohammed Akhiruddin Ibrahim; Azlina Mohamed Nor; Ishak Suliaman; Husniyah Salaeh (University of Malaya, 2024)
Volume :1 No: 1